2013
DOI: 10.1186/1472-6963-13-420
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of the public dental services (PDS) in Cyprus and selected determinants

Abstract: BackgroundCurrently there is a dual system of oral healthcare delivery in Cyprus: the public dental system (PDS) run by the Government and the private system provided by private dental practitioners. Although 83% of the population is entitled to free treatment by the PDS only 10% of the population make use of them. As Cyprus faces now the challenges of the introduction of a new health care system and rising healthcare costs in general, surveys that examine, among other things, the efficiency of the PDS become … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Furthermore, another key finding of the current study is the fact that women visit dentists more frequently than men, which confirms the Statistics of the Dental Services (Ministry of Health), according to which, women in all age groups are more frequent users of dental services than men 4 .…”
Section: Methodssupporting
confidence: 87%
“…Furthermore, another key finding of the current study is the fact that women visit dentists more frequently than men, which confirms the Statistics of the Dental Services (Ministry of Health), according to which, women in all age groups are more frequent users of dental services than men 4 .…”
Section: Methodssupporting
confidence: 87%
“…However, Charalambous et al . [ 30 ] did not find any significant relation between the age of dentists and their efficiency. This can be due to different elements which were assessed in these studies.…”
Section: Discussionmentioning
confidence: 97%
“…This may be due to the fact that females have a higher awareness of and interest in oral health than males (13) . Further, the survey showed no relationship between years of experience and knowledge and practice; this is also reported in a study by Charalambous et al (2013), where no significant relationship was found between the dentists' age and their efficacy (27) . Also, a significant relationship was observed between high levels of practice and knowledge and having a postgraduate degree in orthodontic.…”
Section: Discussionmentioning
confidence: 52%